Copper‐Catalyzed Highly Selective Protoboration of CF3‐Containing 1, 3‐Dienes. Issue 37 (3rd August 2021) - Wu, Juanjuan; Wu, Hongli; Li, Xinzhi; Liu, Xinyu; Zhao, Qian; Huang, Genping; Zhang, Chun
Abstract: The copper‐catalyzed highly selective protoboration of CF3 ‐containing conjugated diene with proton source and B2 Pin2 has been developed. This chemistry could suppress the well‐known defluorination and provide borated reagents with an intact CF3 ‐group. Further studies indicated that the functional group tolerance of this chemistry is very well, and the products could be used as versatile precursors for different types of transformations. Importantly, using chiral diphosphine ligand, we have developed the first example for using such starting material to synthesis allylic boron‐reagents which bearing a CF3 ‐containing chiral center. Notably, the reaction mechanism was intensively studied by DFT calculations, which could reveal the reason that defluorination was inhibited. Abstract : The novel copper‐catalyzed protoboration of CF3 ‐containing 1, 3‐dienes with proton source and B2 Pin2 has been developed. This chemistry afforded the CF3 ‐containing borated products with good selectivity and efficiency.